Stoner sob o peso das sombras - Oliveira Filho, Sérgio Murilo Fontes de (2020)
The aim of this thesis is to conduct a comparative analysis of the novels Stoner, written by American author John Williams, and Sob o peso das sombras, by Brazilian author Francisco José Costa Dantas, originally from the State of Sergipe. Our analysis will focus on the salvation of the protagonists William Stoner and Justino Vieira through literature. We begin by surveying the authors’ respective critiques in order to identify their main characteristics, considering not only the fore listed novels, but also their entire bodies of work. Then, we initiate our analysis highlighting the tremendous effect of books and the act of reading on the trajectory and ultimate self-realization of the characters. In so doing, we discuss certain aspects of the narrators (DAL FARRA, 1978; LEITE, 1987) and present parallels between the concept of culture (BOSI, 1992; EAGLETON, 2011) and a relationship that the act of reading aligns with the origins of the protagonists. Moving onto the theme of salvation, we demonstrate how reading often functions as a refuge from the mediocre lives they lead. To this end, references from Antoine Compagnon (2014), Terry Eagleton (2010), Michel de Certeau (2014), Maurice Blanchot (2011), Jean Marie Goulemot (1996), Umberto Eco (2014) and Roger Chartier (1996) were taken into consideration. In the second chapter, with the help of Tzvetan Todorov (2014), Max Weber (2004), Michel Foucault (2013) and Nadja Hermann (2005), we articulate the broader shift in the concept of salvation in the religious semantic field, (the salvation of the soul after death) to the present semantic field, salvation as both a mitigation of danger or preservation of bodily and spiritual safety, among other possible meanings. We then return to the analysis of the novels to explain the relationship between the lives that William Stoner and Justino Vieira lead and how they read, as their ways of life and reading choices changed both their views on the world (CANDIDO, 2011) and their moral and ethical values (COMPAGNON, 2000) and, ultimately, saved them. Finally, we focus on writing, as both characters are writers. We believe this is also related to the salvation of the protagonists, particularly in the relationship that their works of writing have with death, from Plato (2016) and Jacques Derrida (2015). Thus, this research is a meditation on the potential for transformation and expansion of horizons that literature can have, and on the accompanying importance of narratives about characters who do not adhere to prototypical heroic arcs.